2017
DOI: 10.18632/oncotarget.22030
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of rs1347093 and rs1397529 are associated with lung cancer risk in northeast Chinese population

Abstract: Lung cancer is one of the malignant tumors with the highest morbidity and mortality all over the world. Here we researched the association between two SNPs (rs1347093 in MIR217HG and rs1397529 in Gab1) and the risk of lung cancer in northeast Chinese population, including 825 cases and 766 controls. We carried out χ2 test, unconditional logistic regression analysis and crossover analysis to estimate the relationship between SNPs and lung cancer risk and the interaction between SNPs and smoking on susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the present study, we found that rs1397529 C alleles were risk factors for meningioma. Li et al reported that the MAF of rs1397529 was significantly lower in the case group (5.8%) than in the control group (8.2%); the C allele was a protective factor, and a dominant genetic model of rs1397529 was associated with a reduced risk of lung cancer, compared with the AA genotype in a previous study [ 20 ]. We found 2 genotypes (AA and AC) at this locus, while 3 genotypes (AA, AC, and CC) were found in the study by Li et al The CC genotype in the latter was only 0.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that rs1397529 C alleles were risk factors for meningioma. Li et al reported that the MAF of rs1397529 was significantly lower in the case group (5.8%) than in the control group (8.2%); the C allele was a protective factor, and a dominant genetic model of rs1397529 was associated with a reduced risk of lung cancer, compared with the AA genotype in a previous study [ 20 ]. We found 2 genotypes (AA and AC) at this locus, while 3 genotypes (AA, AC, and CC) were found in the study by Li et al The CC genotype in the latter was only 0.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The Gab1 gene is located on chromosome 4, and its single-nucleotide polymorphisms (SNPs) are reported to be closely related to the susceptibility of several human diseases, such as biliary tract cancer and lung cancer [ 19 , 20 ]. The Gab1 SNPs may be involved in the pathogenesis of human diseases by regulating the expression of key genes of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…GAB1 germline copy number variation is linked to breast cancer risk [ 75 ]. Furthermore, genetic polymorphisms in GAB1 have been reported to increase susceptibility to developing some types of cancer, such as cholangiocarcinoma, meningiomas, and lung cancer [ 76 , 77 , 78 , 79 ]. Interestingly, high levels of GAB1 expression are associated with poor prognosis in patients with gliomas, hepatocellular carcinoma, and ovarian cancer [ 80 , 81 , 82 ].…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers